Ideological critique and dynamics of democracy: critical discourse analysis of the “Pasar Bebas Capres” narrative in revealing oligarchy on the Mata Najwa - Purwaningrum, Prapti Wigati; Harmoko, Danang Dwi (NOTION: Journal of Linguistics, Literature, and Culture, 2025)
This study examines the ideology in the Free Market Presidential Candidate narrative on the Mata Najwa program on Trans 7. Using Fairclough's (2013) Critical Discourse Analysis (CDA) approach, this study investigates how the narrative critiques oligarchic practices and their impact on democracy in Indonesia. This study addresses three main questions: (1) How does the narrative critique oligarchy and its implications for democratic practices? (2) What linguistic and rhetorical strategies are used to convey criticism of the presidential nomination threshold? (3) How do textual discourse, discourse practices, and socio-cultural contexts shape public perceptions of political dynamics? This analysis follows Fairclough's three-dimensional CDA model: textual analysis, discourse practices, and socio-cultural practices. The research findings reveal that the narrative uses sharp diction, satire, and metaphorical language to express concerns and criticisms of the Constitutional Court, the House of Representatives (DPR), and political parties. The narrative reflects public dissatisfaction with political elites and raises concerns about the future of democracy under oligarchic influence. This research contributes to understanding how media narratives function as a critique of political reality as well as a tool to shape public perceptions of democratic practices in Indonesia.